Ethnobotany in the Cumbres de Monterrey National Park, Nuevo León, México - Scott Laura; Cabral Ismael; Cantú César; Villarreal José A; Estrada Eduardo; Yen Carmen (BMC, 2007)
Abstract An ethnobotanical study in the Cumbres de Monterrey National Park (CMNP), Nuevo Leon, Mexico was conducted. In spite of the large area (1,773.7 km2), heterogeneous physiography, contrasting plant communities and high species diversity of the CMNP, very little was previously known about its useful plants. Based on 95 interviews with inhabitants of the region who were 35 years or older, we recorded ethnobotanical data of 240 species (comprising 170 genera and 69 botanical families), and 146 different uses. Most of the cited uses (98) were found to be medicinal ones. Background An ethnobotanical study in the Cumbres de Monterrey National Park (CMNP), Nuevo Leon, Mexico was conducted. In spite of the large area (1,773.7 km2), heterogeneous physiography, contrasting plant communities and high species diversity of the CMNP, very little was previously known about its useful plants. Based on 95 interviews with inhabitants of the region who were 35 years old or older, we recorded ethnobotanical data of 240 species (comprising 170 genera and 69 botanical families), and 146 different uses. Most of the cited uses (98) were found to be medicinal ones. Methods Ninety five inhabitants 35 years old and oldest were interviewed to know what are the main plant uses in the Cumbres de Monterrey National Park. Results and discussion Two hundred and forty species, 170 genera, and 69 families of useful plants and 146 different uses were recorded. We found most of the uses to be medicinal (98), while the rest (48) represent various purposes. Herbaceous plants are the most used, followed by shrubs and trees.